FINANCIAL STIMULUS STRATEGY TO PROMOTE ECONOMIC GROWTH IN THE ECONOMIC CRISIS DUE TO COVID-19 - Hanri Jan Piter; Yudi Satrasna; Guntur Eko Saputro (Karimun University, 2022)
This research was conducted to see how far the implementation of the strategies established by the government, especially financial stimulus and distribution of social assistance. Penelitian ini disusun dengan metode pendekatan deskriptif kualitatif. This study aims to look at the state of the economic crisis due to covid-19, the economic recovery strategy for the welfare of the community. The researcher makes use of method concept in keeping with Andrew J Good Paster that is divided into 3 parts, the primary is the intention to be accomplished is monetary recuperation to obtain people's prosperity and is an duty of the country to prosper its people. The second method is to make budgetary fiscal policies and distribute social assistance to the community quickly and on target. The three tools or facilities are according to government regulations, vaccinations, health workers and volunteers. The implementation of the government's financial stimulus and social assistance program concluded that the government had not been able to fully meet the needs of its citizens in accordance with the implementation of Article 34 of the 1945 Constitution and had not been able to encourage economic growth due to the COVID-19 pandemic. Keywords: Economic Recovery, Social Assistance, Financial Stimulus, Economic Crisis Abstrak Penelitian ini dilakukan untuk melihat sejauh mana implementasi dari strategi-strategi yang telah ditetapkan pemerintah, khususnya stimulus finansial dan penyaluran bansos. Penelitian ini disusun dengan pendekatan deskriptif kualitatif. Penelitian ini bertujuan untuk melihat keadaan krisis ekonomi akibat covid-19, strategi pemulihan ekonomi untuk kesejahteraan masyarakat. Peneliti menggunakan konsep metode yang sesuai dengan Andrew J Good Paster yang terbagi menjadi 3 bagian, yang utama adalah tujuan yang ingin dicapai adalah pemulihan moneter untuk mencapai kemakmuran rakyat dan merupakan kewajiban negara untuk mensejahterakan rakyatnya. Cara kedua adalah membuat kebijakan fiskal anggaran dan menyalurkan bantuan sosial kepada masyarakat secara cepat dan tepat sasaran. Ketiga alat atau fasilitas tersebut sesuai peraturan pemerintah, vaksinasi, tenaga kesehatan dan relawan. Pelaksanaan program stimulus keuangan dan bantuan sosial pemerintah menyimpulkan bahwa pemerintah belum dapat sepenuhnya memenuhi kebutuhan warganya sesuai dengan pelaksanaan Pasal 34 UUD 1945 dan belum mampu mendorong pertumbuhan ekonomi karena pandemi COVID-19. Kata Kunci: Pemulihan Ekonomi, Bantuan Sosial, Stimulus Keuangan, Krisis Ekonomi